Evaluation of Capping Materials to Reduce Zinc Flux from Sediments in a Former Mining Pit Lake. (22nd December 2021) - Cervi, Eduardo Cimino; Hudson, Michelle; Rentschler, Alison; Clark, Sean; Brown, Steven S.; Burton, G. Allen
Abstract: Wilson Mine is a former vanadium mine site located in the Ouachita Mountains near Hot Springs, Arkansas. The site, which drains via two streams to Lake Catherine, has undergone extensive reclamation to significantly reduce groundwater and surface water contact with mine spoils. One of the streams passes through a former mine pit forming East Wilson Pond, and flux from pit lake sediments can result in elevated metal, that is, zinc (Zn), concentrations in overlying water. To mitigate potential risks, an investigation was conducted to evaluate the efficacy of capping materials for partitioning Zn‐contaminated sediments from overlying water in East Wilson Pond. A 28‐day laboratory study compared the effectiveness of capping materials including combinations of limestone, bentonite clay, and gravel for mitigating Zn flux, including under reasonable worst‐case conditions (pH 5.5) encountered in the hypolimnion. Dissolved Zn was monitored over time in overlying water and in sediment porewaters within untreated controls and within the capping layer of treated systems. The use of limestone and/or bentonite clay improved buffering capacity compared to the noncapped control, and pH declined gradually but only modestly in the overlying water and porewater of all treated systems. Concentrations of Zn in overlying water of the noncapped control increased from approximately 30 to 100 µg/L during the study period, while concentrations in the overlying water and porewater of systems containing capping materials remained low (10–30 µg/L). The results demonstrated the effectiveness of the capping materials for neutralizing pH and reducing Zn flux, and a three‐layer cap consisting of limestone (top) + bentonite clay (middle) + gravel (bottom) was determined to be most effective. These results were used to inform the selection of materials for the application of a cap to reduce Zn flux from the pit lake sediments. Environ Toxicol Chem 2022;41:193–200. © 2021 SETAC